2011
DOI: 10.1093/glycob/cwr187
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-specific lectin from the mushroom Hygrophorus russula

Abstract: A lectin was purified from the mushroom Hygrophorus russula by affinity chromatography on a Sephadex G-50 column and BioAssist S cation exchange chromatography and designated H. russula lectin (HRL). The results of sodium dodecyl sulfate-polyaclylamidegel electrophoresis, gel filtration and matrix-assisted laser desorption ionization time-of-flight mass spectrometry of HRL indicated that it was composed of four identical 18.5 kDa subunits with no S-S linkage. Isoelectric focusing of the lectin showed bands nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…From fruiting bodies of the basidiomycetes Hygrophorus russula and Grifola frondosa, two mannose-specific lectins, termed H. russula lectin (HRL) and G. frondosa lectin (GFL), were isolated and characterized (Nagata et al 2005;Suzuki et al 2012). The amino acid sequence of these proteins is related to that of Jacalin from plants, and some plant members of this lectin family have recently been shown to protect the producing plants from herbivorous insects (Al Atalah et al 2014).…”
Section: Additional Families Of Potential Fungal Defense Lectinsmentioning
confidence: 99%
“…From fruiting bodies of the basidiomycetes Hygrophorus russula and Grifola frondosa, two mannose-specific lectins, termed H. russula lectin (HRL) and G. frondosa lectin (GFL), were isolated and characterized (Nagata et al 2005;Suzuki et al 2012). The amino acid sequence of these proteins is related to that of Jacalin from plants, and some plant members of this lectin family have recently been shown to protect the producing plants from herbivorous insects (Al Atalah et al 2014).…”
Section: Additional Families Of Potential Fungal Defense Lectinsmentioning
confidence: 99%
“…HepG2 and MCF7 tumor cell lines (Wang et al, 2000;Zhang et al, 2009;Zhao et al, 2009) After we had commenced the present study on NHRL, a report (Suzuki et al, 2012). Both HRL and NHRL were adsorbed on cationic (S and SP) exchangers.…”
Section: Characterization Of Isolated Lectin the Isolated Lectin Nhrlmentioning
confidence: 85%
“…HRL and NHRL were similar in subunit molecular size and carbohydrate specificity. When the sequence of the first thirty N-terminal residues in NHRL is compared with that of the H. russula lectin reported in the literature (Suzuki et al, 2012), eleven different amino acid residues (shown in italics) are observed at corresponding positions in the sequences, indicating a 63.3% identity (Fig. 5).…”
Section: Characterization Of Isolated Lectin the Isolated Lectin Nhrlmentioning
confidence: 95%
See 2 more Smart Citations